Technical note: Proton beam dosimetry at ultra‐high dose rates (FLASH): Evaluation of GAFchromic™ (EBT3, EBT‐XD) and OrthoChromic (OC‐1) film performances. Issue 4 (1st March 2022) - Villoing, Daphnée; Koumeir, Charbel; Bongrand, Arthur; Guertin, Arnaud; Haddad, Ferid; Métivier, Vincent; Poirier, Freddy; Potiron, Vincent; Servagent, Noël; Supiot, Stéphane; Delpon, Grégory; Chiavassa, Sophie
Abstract: Purpose: The ARRONAX cyclotron facility offers the possibility to deliver proton beams from low to ultra‐high dose rates (UHDR). As a good control of the dosimetry is a prerequisite of UHDR experimentations, we evaluated in different conditions the usability and the dose rate dependency of several radiochromic films commonly used for dosimetry in radiotherapy. Methods: We compared the dose rate dependency of three types of radiochromic films: GAFchromic™ EBT3 and GAFchromic™ EBT‐XD (Ashland Inc., Wayne, NJ, USA), and OrthoChromic OC‐1 (OrthoChrome Inc., Hillsborough, NJ, USA), after proton irradiations at various mean dose rates (0.25, 40, 1500, and 7500 Gy/s) and for 10 doses (2–130 Gy). We also evaluated the dose rate dependency of each film considering beam structures, from single pulse to multiple pulses with various frequencies. Results: EBT3 and EBT‐XD films showed differences of response between conventional (0.25 Gy/s) and UHDR (7500 Gy/s) conditions, above 10 Gy. On the contrary, OC‐1 films did not present overall difference of response for doses except below 3 Gy. We observed an increase of the netOD with the mean dose rate for EBT3 and EBT‐XD films. OC‐1 films did not show any impact of the mean dose rate up to 7500 Gy/s, above 3 Gy. No difference was found based on the beam structure, for all three types of films. Conclusions: EBT3 and EBT‐XD radiochromic films should be used with caution for the dosimetry of UHDR proton beams over 10 Gy. Their overresponse, which increases with mean dose rate and dose, could lead to non‐negligible overestimations of the absolute dose. OC‐1 films are dose rate independent up to 7500 Gy/s in proton beams. Films response is not impacted by the beam structure. A broader investigation of the usability of OC‐1 films in UHDR conditions should be conducted at intermediate and higher mean dose rates and other beam energies.